Learning Quality Management based on Kind and Strong Character in Daarut Tauhiid Vocational School Bandung - Maulana, Irwan; Sintawati, Fairus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
Learning quality service management based on character in vocational high school had important role to produce school graduates who had skills and characters. Daarut Tauhiid Vocational High School had kind and strong character (BaKu) concept implemented into all learning activities. This study aimed to describe Learning quality service management based on characters of kind and strong in Daarut Tauhiid Vocational High School. The method used was descriptive qualitative approach. Data collection techniques used were observation, interview, study documentation and data validation test by data collection, data reduction, data display, and data verification. The result of this study showed that learning quality service plan based on kind and strong characters formulated by the principal and teacher council through character learning program (PBM Berkarakter) and the programs supported such as industries visitation, tahsin and tahfidz al-Quran, literacy, entrepreneurship skill, and skill certification. Learning quality service based on kind and strong characters implementation conducted through character learning program (PBM Berkarakter) in the class and habituation out of class. The implementation conducted based on the standard operational procedure (SOP). The assessment conducted through daily assessment, program assessment, and academic assessment. Daily assessment meant to assess students’ character and academic, weekly assessment conducted through self-assessment and peer assessment (PD-PAT), monthly assessment conducted by all Daarut Tauhiid civitas and the representation of students assessed the teacher by giving recommendation and critics, mid semester assessments and final semester assessment through mid semester assessment test (PTS) and final semester assessment test (PAS). By this, learning quality management based on kind and strong characters ran well.